2011
DOI: 10.3858/emm.2011.43.9.056
|View full text |Cite
|
Sign up to set email alerts
|

Continuous hypoxia attenuates paraquat-induced cytotoxicity in the human A549 lung carcinoma cell line

Abstract: Paraquat (1,1'-dimethyl-4,4'-bipyridinium dichloride; PQ), an effective and widely used herbicide, was commercially introduced in 1962. It is reduced by the electron donor NADPH, and then reduced PQ transfers the electrons to molecular oxygen, resulting in the production of reactive oxygen species (ROS), which are related to cellular toxicity. However, the influence of continuous hypoxia on PQ-induced ROS production has not fully been investigated. We evaluated in vitro the protective effect of continuous hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…In this scenario, paraquat (PQ) intoxication is a serious public health problem because of its high mortality index, mainly due to the lack of an effective antidote or treatment, which is associated with its wide use even in countries where its application is forbidden. [36][37][38][39][40] One of the main mechanism for PQ toxicity is associated with the redox cycle of PQ, where formation of superoxide anion, singlet oxygen, and other reactive oxygen species (ROS) occurs. Higher levels of these ROS lead to many deleterious effects, including lipid peroxidation in cells and tissue, protein damage, and depletion of NADPH.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, paraquat (PQ) intoxication is a serious public health problem because of its high mortality index, mainly due to the lack of an effective antidote or treatment, which is associated with its wide use even in countries where its application is forbidden. [36][37][38][39][40] One of the main mechanism for PQ toxicity is associated with the redox cycle of PQ, where formation of superoxide anion, singlet oxygen, and other reactive oxygen species (ROS) occurs. Higher levels of these ROS lead to many deleterious effects, including lipid peroxidation in cells and tissue, protein damage, and depletion of NADPH.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that paraquat (PQ) is a potent ROS inducer in different epithelial cell lines [12][13][14] and is associated with cellular cytoxicity. However, there has been no study into whether PQ can induce MUC gene expression or not, so in this study we investigated the effects of PQ on Bronchial epithelial BEAS-2B cells.…”
mentioning
confidence: 99%
“…[8][9][10][11] MUC5AC is a hallmark gene, and considered the most phenotypical gene in respiratory diseases; it accumulates in respiratory tract can lead to symptoms such as chronic cough and excessive sputum production. Previous studies showed that paraquat (PQ) is a potent ROS inducer in different epithelial cell lines [12][13][14] and is associated with cellular cytoxicity. However, there has been no study into whether PQ can induce MUC gene expression or not, so in this study we investigated the effects of PQ on Bronchial epithelial BEAS-2B cells.…”
mentioning
confidence: 99%
“…When these antioxidants are imbalanced, there will be airway inflammation, airway hyperresponsiveness and tissue damage, neutrophil infiltration and ultimately the formation of lung injury. 2,6,33 In our study, the results showed that the levels of ROS were markedly increased in the PQ group. In the rat model of PQ poisoning, MDA levels increased and GSH and SOD levels decreased at each time point.…”
Section: Zhu Et Almentioning
confidence: 58%
“…In this process, PQ consumes nicotinamide adenine dinucleotide phosphate and cytochrome P450 reductase, increasing superoxide anion and hydrogen peroxide levels through the disproportionation of hydrogen peroxide to generate hydroxyl and other radicals, constituting a reactive oxygen species (ROS) system. 6 ROS can activate lipid peroxidation and increase malondialdehyde (MDA) levels in this process. The level of MDA indirectly reflects the degree of peroxidation, and elevated MDA levels can also cause cell metabolism disorders.…”
mentioning
confidence: 99%